Adaptive Steganographic Technique for Digital Images Based on The Least Significant Bit Substitution - Ekhlas Ghaleb Abdulkadhim; Zaman Mahdi Abbas; Muqdad Abdulraheem Hayder (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2025)
It has become natural to retain most of the information electronically, due thanks to developments and improvements in information and communication technology. Thus, information security has become a major significant problem. Aside from cryptography, this study employs two strategies could be utilized to share information securely to ensure secure information sharing. Cryptography and steganography are two of these mechanisms. Using an encryption key known to both the receiver and the sender, the message isencrypted. Without the encryption key, no one will be able to read the message. Thus, this study proposes an efficient method based on the Least Significant Bit (LSB). Employing the LSB substitution approach ensures reliability, since as it can decrease the embedding error rate. For image-based steganography, our algorithm is formed by exploiting LSB substitution combined with a Multi-Level Encryption Algorithm (MLEA) the algorithm combines LSB substitution with a Multi-Level Encryption Algorithm (MLEA), Secret Key (SK), transposition, and flipping. According to the experimental results, the proposed method is efficient and produces effectualeffective outcomes. Several Quality Assessment Metrics (QAMs) evaluate 125 unique RGB images with varying degrees of hidden information, such as including PSNR, Contrast, and Image Histogram. Besides security analysis, the results prove that the proposed approach withstands RS analysis with great strength. Furthermore, our experimental results demonstrate that this study thoroughly tests the proposed technique with several steganographic and statistical indicators. When it compared to those of other available approaches, the analysis confirms the practicality of our method, and which is easy to implement and superior.